Esporas triletes verrucosas de la Formación Lagarcito (Albiano?) Sierra de Guayaguas, Provincia de San Juan, Argentina. Análisis bioestratigráfico - Mego, Natalia (2013)
Verrucate trilete spores from the Lagarcito Formation (Albian?) Sierra de Guayaguas, San Juan Province, Argentina. Biostratigraphic analysis. A detailed study of the systematics of thirteen species of verrucate trilete spores recovered from the Lagarcito Formation is presented. Taxonomic studies of these types of spores with great morphological diversity are very important as they constitute a useful contribution for the clarification of many misidentifications usually very common within this morphologic group. The Lagarcito Formation is part of the El Gigante Group, formed by continental sediments of fluvio-deltaic origin deposited in an extensional basin. The material was collected in a section exposed in the eastern side of the Sierra de Guayaguas, southeast of the San Juan province and corresponds to shallow lacustrine sediments. The following species are described and illustrated: Concavissimisporites penolaensis Dettmann, Concavissimisporites punctatus (Delcourt & Sprumont) Brenner, Concavissimisporites variverrucatus (Couper) Brenner, Concavissimisporites sp., Converrucosisporites cf. C. exquisitus Singh, Impardecispora apiverrucata (Couper) Venkatachala, Kar & Raza, Impardecispora texensis Srivastava, Impardecispora sp., Leptolepidites major Couper, Leptolepidites verrucatus Couper, Reyrea polymorphus Herngreen, Verrucosisporites rotundus Singh, Verrucosisporites varians Volkheimer. Within the palynoflora the verrucate trilete spores are abundant and correspond to the fern families: Lycopodiaceae, Selaginellaceae, Cyatheaceae, Osmundaceae, Dicksoniaceae and Schizaeaceae, indicative of local humid conditions near the lacustrine bodies. Based on the analysis of the occurrence and biostratigraphical value of the studied species in different Lower Cretaceous basins in Argentina and other related places, an Aptian-Albian range is concluded for the verrucate spore association recovered from the Lagarcito Formation. The present systematic study provides also new insight to the vegetal diversity developed during the Early Cretaceous in central-western Argentina.